Erlotinib combined with bevacizumab and chemotherapy in first line osimertinib-resistant NSCLC patient with leptomeningeal metastasis: A case report. Issue 44 (5th November 2021) - Wang, Musen; Zhu, Fuxin; Luo, Ningning; Li, Mengmeng; Qi, Yingxue; Wang, Mingbo
Abstract: Rationale: Leptomeningeal metastasis (LM) is a fatal complication of advanced non-small cell lung cancer (NSCLC) with a poor prognosis. Osimertinib is a promising option for NSCLC with LM harboring epidermal growth factor receptor (EGFR) mutation. However, therapeutic approaches remain a challenge for osimertinib resistant NSCLCs with LM. Although studies have reported that the first/second-generation EGFR-tyrosine kinase inhibitors were active against osimertinib-resistant NSCLC with EGFR C797S and sensitive mutation (SM), the resistance inevitably occurred due to the development of the EGFR SM/C797S/T790M triple mutations. Patient concerns: A 48-year-old woman was diagnosed with stage IV lung adenocarcinoma harboring the EGFR mutation in the combination of chest computed tomography, biopsy and amplification refractory mutation system-polymerase chain. One year and a half after oral administration of osimertinib, the patient progressed to extensive LM. Diagnoses: Magnetic resonance images of the brain showed extensive LM. Exfoliated tumor cells from cerebrospinal fluid (CSF) were positive detected by lumbar puncture and the cytology examination. EGFR mutations (exon19 E746_T751delinsI and exon20 C797S) in CSF circulating tumor DNA were detected by next-generation sequencing (NGS). Interventions: Pemetrexed (800 mg day 1), cis-platinum (40 mg day 1-3) combined with bevacizumab (400 mg day 1) every 3 weeks were administered to the patient. After 1 cycle, due to optic nerve invasion, erlotinib was applied 150 mg/d combined with previous regimen. The patient continued erlotinib monotherapy after 6 cycles. Outcomes: After LM, erlotinib combined with pemetrexed, cis-platinum and bevacizumab were administered to the patient for 4.25 months based on the CSF NGS. Then, the patient continued erlotinib monotherapy and appeared disease progression after 10 months. The overall survival is 35 months. Lessons: LM is a fatal complication of advanced NSCLC with a poor prognosis. NGS profiling of CSF circulating tumor DNA is important in NSCLC patients with LM and erotinib plus bevacizumab and chemotherapy is a promising option for patients with LM harboring EGFR C797S/SM.